Bimetal-catalyzed magnesium-based hydrogen storage material and preparation method thereof
By introducing the bimetallic catalyst TiO2/C/Ni into magnesium hydride (MgH2), the problem of slow kinetics of MgH2 during low-temperature hydrogen absorption and high-temperature de-release is solved, and more efficient hydrogen storage and release is achieved, and cycle stability is improved.
Patent Information
- Application Number
- CN202411741023.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-29
- Publication Date
- 2025-03-18
AI Technical Summary
Magnesium hydride (MgH2) has a slow rate of hydrogen absorption and release during low-temperature hydrogen absorption and high-temperature de-release, and has poor thermal stability at high-temperature, which limits its widespread use in practical applications.
The bimetallic catalyst TiO2/C/Ni is used to introduce it into MgH2, thereby achieving trace and efficient catalysis of MgH2 and improving its hydrogen absorption and release kinetic performance.
The dehydrogenation activation energy of MgH2 is significantly reduced, and its hydrogen storage performance and hydrogen absorption and discharge cycle stability are improved. The initial dehydrogenation temperature is reduced to 185℃, and the capacity attenuation rate is only 6% after 50 cycles.
Smart Images

Figure CN119637807A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of hydrogen energy and relates to a bimetallic catalyzed magnesium-based hydrogen storage material and a preparation method thereof. Background Art
[0002] As an efficient and low-carbon energy carrier, hydrogen plays a vital role in the transition from high-carbon emissions to low-carbon emissions, and its rapid development carries the important mission of achieving carbon neutrality. In recent years, the rapid development of traditional solid-state hydrogen storage materials has provided safer and more efficient hydrogen storage. Among them, magnesium hydride (MgH2) has attracted widespread attention due to its high hydrogen storage capacity (7.6wt.% H2), abundant resources and environmental protection characteristics. However, during the hydrogen absorption and release process of MgH2 at low temperature and high temperature, its hydrogen absorption and desorption rate is slow and its high-temperature thermal stability is poor, which limits its widespread use in practical applications.
[0003] Therefore, how to effectively improve the performance of magnesium-based hydrogen storage materials so that magnesium hydride (MgH2) can effectively solve the problems of slow hydrogen absorption and desorption rate and poor high-temperature thermal stability during low-temperature hydrogen absorption and high-temperature desorption is desired by technicians in this field.
[0004] In view of this, the present invention is proposed. Summary of the invention
[0005] The present invention aims to provide a bimetallic catalyzed magnesium-based hydrogen storage material and a preparation method and application thereof, so as to improve the above-mentioned problems existing in the prior art.
[0006] In order to achieve the above purpose, the following technical solutions are adopted:
[0007] The first object of the present invention is to provide a bimetallic catalyzed magnesium-based hydrogen storage material, wherein the magnesium-based hydrogen storage material is a composite formed by magnesium hydride and a catalyst;
[0008] The catalyst is a bimetallic catalyst TiO2 / C / Ni formed by loading nickel and titanium dioxide on a carbon matrix.
[0009] Further, based on the above technical solution of the present invention, the mass content of the catalyst in the magnesium-based hydrogen storage material is 0-10wt% and not 0wt%, preferably 3-8wt%, and more preferably 8wt%.
[0010] Furthermore, based on the above technical solution of the present invention, taking the mass of the bimetallic catalyst TiO2 / C / Ni as 100%, the bimetallic catalyst TiO2 / C / Ni contains the following components in mass fractions: Ni 30-35%, TiO2 40-45%, and C 20-30%.
[0011] Further, based on the above technical solution of the present invention, the preparation method of the bimetallic catalyst TiO2 / C / Ni comprises the following steps:
[0012] (a) providing a first mixed solution formed of a titanium source and an ethylene glycol solution, and a second mixed solution formed of a nickel source and an ethylene glycol solution;
[0013] (b) slowly adding the second mixed solution into the first mixed solution, stirring and heating to allow the mixture to react, thereby obtaining a mixed solution product;
[0014] (c) subjecting the mixed solution product to solid-liquid separation, and washing and drying the separated solid product to obtain a precursor Ti-EG-Ni;
[0015] (d) The precursor Ti-EG-Ni is calcined in a protective atmosphere to obtain a bimetallic catalyst TiO2 / C / Ni.
[0016] Further, based on the above technical solution of the present invention, in step (a), the titanium source includes at least one of tetrabutyl titanate, titanium sulfate or titanium isopropoxide;
[0017] And / or, in step (a), the nickel source comprises at least one of nickel acetate tetrahydrate, nickel nitrate or nickel chloride;
[0018] And / or, in step (b), the stirring speed is 250-450 rpm, the time is 10-12 h, and the reaction temperature is 30-50°C.
[0019] Further, based on the above technical solution of the present invention, in step (c), the solvent used for washing includes anhydrous ethanol;
[0020] And / or, in step (c), the drying is vacuum drying, the vacuum drying temperature is 60-80° C., and the time is 10-12 h.
[0021] and / or, in step (d), the calcination temperature is 500-600° C., the calcination time is 2.5-3 h, and the heating rate to the calcination temperature is 3-8° C. / min;
[0022] And / or, in step (d), the protective atmosphere comprises at least one of nitrogen, argon or helium, preferably nitrogen.
[0023] Further, on the basis of the above technical solution of the present invention, the magnesium hydride is prepared by hydrogenation combustion synthesis method;
[0024] And / or, the initial desorption temperature of the magnesium-based hydrogen storage material is at least 185°C.
[0025] The second object of the present invention is to provide a method for preparing a bimetallic catalyzed magnesium-based hydrogen storage material, comprising the following steps:
[0026] The bimetallic catalyst TiO2 / C / Ni and magnesium hydride are evenly mixed by ball milling to obtain a magnesium-based hydrogen storage material.
[0027] Furthermore, based on the above technical solution of the present invention, the ball-to-material ratio used in the ball milling process is (25-35):1, the rotation speed is 350-450rpm, the ball milling is 8-12h, alternating forward and reverse rotation, and stopping for 6min every 30min of work.
[0028] The third object of the present invention is to provide the application of the above-mentioned bimetallic catalyzed magnesium-based hydrogen storage material or the bimetallic catalyzed magnesium-based hydrogen storage material prepared by the above-mentioned preparation method in the field of hydrogen storage.
[0029] Compared with the prior art, the technical solution of the present invention has at least the following technical effects:
[0030] (1) The present invention provides a bimetallic catalyzed magnesium-based hydrogen storage material, which is mainly composed of a composite formed by magnesium hydride (MgH2) and a catalyst, wherein the catalyst is a bimetallic catalyst TiO2 / C / Ni formed by nickel (Ni) and titanium dioxide supported (TiO2) on a carbon matrix (C); by introducing the bimetallic catalyst TiO2 / C / Ni into MgH2, a trace amount of efficient catalysis of MgH2 is achieved, and while the hydrogen storage capacity of MgH2 is not excessively lost, an excellent catalytic effect can be achieved, so that the prepared magnesium-based hydrogen storage material MgH2-TiO2 / C / Ni exhibits excellent hydrogen storage performance and hydrogen absorption and desorption cycle stability.
[0031] In particular, the present invention significantly reduces the dehydrogenation activation energy (60.526 kJ / mol) of MgH2 by introducing 8 wt.% TiO2 / C / Ni catalyst into MgH2, accelerates the hydrogen absorption and desorption kinetics of MgH2, and exhibits better hydrogen storage performance than other catalysts.
[0032] At the same time, the magnesium-based hydrogen storage material MgH2-8 wt.% TiO2 / C / Ni of the present invention exhibits excellent catalytic performance, with an initial dehydrogenation temperature of 185°C, and maintains good kinetic stability and capacity retention after multiple cycles, with a capacity decay rate of only 6% after 50 cycles. It also has excellent hydrogen storage performance: it can absorb 5.72wt.% H2 within 20 seconds at 150°C, and even at a low temperature of 75°C, it can absorb 4.33wt.% H2 within 3000 seconds. At the same time, it can release 6.17wt.% H2 within 300 seconds at 300°C, and 2.1wt.% H2 within 3000 seconds at 225°C.
[0033] (2) The bimetallic catalyzed magnesium-based hydrogen storage material provided by the present invention was characterized by XRD and TEM. The results showed that during the hydrogen absorption and release process, the magnesium-based hydrogen storage material formed a multi-element, multi-valent environment (including Mg2Ni / Mg2NiH4 (hydrogen pump effect) and multivalent Ti), the elements were evenly distributed, and the carbon material provided a protective mechanism. These factors together contributed to the excellent hydrogen storage performance of the magnesium-based hydrogen storage material.
[0034] (3) The present invention provides a method for preparing a bimetallic catalyzed magnesium-based hydrogen storage material, wherein the bimetallic catalyst TiO2 / C / Ni is introduced into the MgH2 system by a high-energy ball milling method, so that the prepared magnesium-based hydrogen storage material MgH2-TiO2 / C / Ni exhibits excellent hydrogen storage performance, thereby improving the hydrogen absorption and desorption cycle stability of the magnesium-based hydrogen storage material. BRIEF DESCRIPTION OF THE DRAWINGS
[0035] Figure 1a A simple schematic diagram of the synthesis of the TiO2 / C / Ni catalyst of the present invention;
[0036] Figure 1b is the X-ray diffraction (XRD) pattern of the precursor Ti-EG-Ni of the present invention;
[0037] Figure 1c is the X-ray diffraction (XRD) pattern of the catalyst TiO2 / C / Ni of the present invention;
[0038] Figure 2a The scanning electron microscope (SEM) spectrum of the precursor Ti-EG-Ni of the present invention;
[0039] Figure 2b The scanning electron microscope (SEM) spectrum of the TiO2 / C / Ni catalyst of the present invention;
[0040] Figure 3a XRD patterns of the MgH2-8wt.%TiO2 / C / Ni composite material of the present invention at different stages;
[0041] Figure 3b The XRD patterns of the MgH2-8wt.%TiO2 / C / Ni composite material of the present invention at different stages of local amplification;
[0042] Figure 4 A high-resolution transmission electron microscopy image (HRTEM) of the rehydrogenated MgH2-8wt.%TiO2 / C / Ni composite material of the present invention;
[0043] Figure 5 The selected area electron diffraction (SAED) of the rehydrogenated MgH2-8wt.%TiO2 / C / Ni composite material of the present invention;
[0044] Figure 6 is an EDS element distribution diagram of the elements magnesium, carbon, nickel and titanium in the rehydrogenated MgH2-8wt.%TiO2 / C / Ni composite material of the present invention;
[0045] Figure 7 DSC test curves of MgH2 composite materials doped with TiO2 / C / Ni in different proportions (x wt.%=0, 3, 5, 8, 10) of the present invention;
[0046] Figure 8 It is a comparison diagram of TPD curves of MgH2-TiO2 / C / Ni, MgH2-Ni and MgH2-TiO2 / C composite materials of the present invention;
[0047] Figure 9a DSC curves of MgH2-8 wt.%TiO2 / C / Ni at different heating rates of the present invention;
[0048] Figure 9b It is a curve fitted by the Kissinger equation at different heating rates for MgH2-8 wt.%TiO2 / C / Ni of the present invention;
[0049] Fig.10a Isothermal dehydrogenation curves of MgH2-8 wt.%TiO2 / C / Ni at different temperatures of the present invention;
[0050] Fig.10b The isothermal hydrogenation curves of MgH2-8wt.%TiO2 / C / Ni at different temperatures of the present invention;
[0051] Fig.11a The kinetic curve of 50 hydrogen absorption and desorption cycles of the MgH2-8wt.%TiO2 / C / Ni composite material of the present invention at 275°C;
[0052] Fig.11b The figure shows the relationship between the hydrogen absorption and desorption capacity and the number of cycles of the MgH2-8 wt.%TiO2 / C / Ni composite material of the present invention. DETAILED DESCRIPTION
[0053] In order to make the purpose, technical scheme and advantages of the present invention clearer, the technical scheme in the embodiment of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention. Based on the embodiments in the present invention, all other embodiments obtained by ordinary technicians in the field without making creative work are within the scope of protection of the present invention. The process parameters of the following embodiments that do not specify specific conditions are usually based on conventional conditions.
[0054] The endpoints and any values of the ranges disclosed in the present invention are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be regarded as specifically disclosed in the present invention.
[0055] According to a first aspect of the present invention, there is provided a bimetallic catalyzed magnesium-based hydrogen storage material, wherein the magnesium-based hydrogen storage material is a composite formed by magnesium hydride (MgH2) and a catalyst;
[0056] The catalyst is a bimetallic catalyst TiO2 / C / Ni formed by loading nickel (Ni) and titanium dioxide (TiO2) on a carbon matrix (C).
[0057] Specifically, the catalyst of the present invention combines two metal elements, nickel and titanium, wherein nickel exists in the form of metal particles and titanium exists in the form of metal oxide titanium dioxide (TiO2), and forms a bimetallic catalyst TiO2 / C / Ni by loading (dispersing) nickel and titanium dioxide in a carbon matrix.
[0058] The bimetallic catalyst TiO2 / C / Ni is introduced into MgH2 to achieve trace and efficient catalysis of MgH2, without excessively losing the hydrogen storage capacity of MgH2, while achieving excellent catalytic effect. The magnesium-based hydrogen storage material has good hydrogen absorption and desorption cycle stability, effectively solving the problem of slow low-temperature hydrogen absorption and high-temperature dehydrogenation kinetics of MgH2.
[0059] The mass content of the bimetallic catalyst TiO2 / C / Ni in the magnesium-based hydrogen storage material will affect the dehydrogenation performance of the magnesium-based hydrogen storage material, so the mass content of the bimetallic catalyst TiO2 / C / Ni in the magnesium-based hydrogen storage material is further limited.
[0060] As an optional embodiment of the technical solution of the present invention, the mass content of the bimetallic catalyst TiO2 / C / Ni in the magnesium-based hydrogen storage material is 0-10wt% and is not equal to 0wt%, preferably 3-8wt%, and more preferably 8wt%. Typical but non-limiting mass contents are 0.5wt%, 1wt%, 2wt%, 3wt%, 4wt%, 5wt%, 6wt%, 7wt%, 8wt%, 9wt% or 10wt%, etc.
[0061] By further limiting or optimizing the mass content of the bimetallic catalyst TiO2 / C / Ni in the magnesium-based hydrogen storage material, the magnesium-based hydrogen storage material has excellent comprehensive dehydrogenation performance.
[0062] The relative mass ratio of TiO2, Ni and C in the bimetallic catalyst TiO2 / C / Ni was further optimized.
[0063] As an optional implementation of the technical solution of the present invention, the bimetallic catalyst TiO2 / C / Ni is designed to contain the following components in mass fractions, based on the mass of the bimetallic catalyst TiO2 / C / Ni being 100%: the mass fraction of Ni is 30-35%, the mass fraction of TiO2 is 40-45%, and the mass fraction of C is 20-30%. Therefore, the mass fraction of Ni is typically but not limited to 30%, 31%, 32%, 33%, 34% or 35%, etc., the mass fraction of TiO2 is typically but not limited to 40%, 41%, 42%, 43%, 44% or 45%, etc., and the mass fraction of C is typically but not limited to 20%, 21%, 22%, 23%, 24%, 25%, 26%, 27%, 28%, 29% or 30%, etc.
[0064] By further limiting the mass contents of TiO2, Ni and C in the bimetallic catalyst TiO2 / C / Ni, TiO2 and Ni can be better dispersed in the amorphous carbon C (formed by carbonization of ethylene glycol).
[0065] As an optional implementation of the technical solution of the present invention, the preparation method of the bimetallic catalyst TiO2 / C / Ni comprises the following steps:
[0066] (a) providing a first mixed solution formed of a titanium source and an ethylene glycol solution, and a second mixed solution formed of a nickel source and an ethylene glycol solution;
[0067] (b) slowly adding the second mixed solution into the first mixed solution, stirring and heating to allow the mixture to react, thereby obtaining a solution product;
[0068] (c) subjecting the solution product to solid-liquid separation, and washing and drying the separated solid product to obtain a precursor Ti-EG-Ni;
[0069] (d) The precursor Ti-EG-Ni is calcined in a protective atmosphere to obtain a bimetallic catalyst TiO2 / C / Ni.
[0070] Steps (a), (b) and (c) in the preparation method are mainly to prepare the catalyst precursor Ti-EG-Ni. The specific synthesis mechanism is: a nickel source (e.g., Ni(CH3COO)2·4H2O) and a titanium source (e.g., Ti(OC4H9)4) are dissolved in an ethylene glycol solution at a certain molar ratio, and ethylene glycol is used as a solvent and a ligand to react with Ti 4+ and Ni 2+ The reaction formed the precursor Ti-EG-Ni with a smooth tubular micelle structure.
[0071] Based on the successful synthesis of the precursor Ti-EG-Ni, step (d) is mainly to calcine the precursor Ti-EG-Ni. During this process, the organic ethylene glycol in the precursor Ti-EG-Ni is thermally decomposed into a carbon material (carbon matrix), so that the nickel and titanium dioxide nanoparticles are evenly distributed in the above carbon matrix, thereby realizing the conversion of the precursor Ti-EG-Ni to the bimetallic catalyst TiO2 / C / Ni. At the same time, the product morphology changes from a smooth tubular micelle structure to a rough rod-like structure, and many small nanoparticles are dispersed on the rough surface.
[0072] It should be noted that the introduction of ethylene glycol plays an important role in the preparation process of the entire bimetallic catalyst TiO2 / C / Ni. First, in the process of forming the precursor Ti-EG-Ni, the ethylene glycol molecules undergo self-assembly synthesis with the Ti ions and Ni ions in the solution; secondly, in the process of transforming the precursor Ti-EG-Ni into the bimetallic catalyst TiO2 / C / Ni, the key role of ethylene glycol as an organic solvent in the formation of ultrafine nanoparticles and the carbonization of ethylene glycol itself enable the uniform distribution of Ni and TiO2 nanoparticles in the carbon matrix, and many small nanoparticles are dispersed on the rough surface, which is also reflected in the SEM and TEM of the material. In addition, when the bimetallic catalyst TiO2 / C / Ni is subsequently introduced into MgH2, the carbon material (carbon matrix) generated in situ in the bimetallic catalyst TiO2 / C / Ni has an inhibitory effect on the particle agglomeration phenomenon caused by the magnesium-based hydrogen storage material MgH2-TiO2 / C / N (i.e., the composite material formed by MgH2 and the bimetallic catalyst TiO2 / C / Ni) during the hydrogen absorption and desorption process. This is also a factor that maintains the stability of the composite material very well, which is conducive to improving the stability of the hydrogen absorption and desorption cycle of the magnesium-based hydrogen storage material. If the ethylene glycol solution is not introduced during the preparation of the bimetallic catalyst, the above effect is difficult to achieve, and the hydrogen storage performance of the resulting magnesium-based hydrogen storage material will also be significantly reduced.
[0073] As an optional implementation of the technical solution of the present invention, in step (a), the titanium source includes tetrabutyl titanate, titanium sulfate or titanium isopropoxide.
[0074] As an optional implementation of the technical solution of the present invention, in step (a), the method for preparing the first mixed solution includes the following steps: respectively measuring an appropriate amount of ethylene glycol (CH2OH)2 solution and an appropriate amount of tetrabutyl titanate Ti(OC4H9)4 solution, mixing the two evenly, stirring and heating to the reaction temperature at the same time.
[0075] Specifically, a pipette is used to measure an appropriate amount of ethylene glycol (CH2OH)2 solution and an appropriate amount of tetrabutyl titanate Ti(OC4H9)4 solution. While the ethylene glycol solution is magnetically stirred by a magnetic rotor, the tetrabutyl titanate solution is added dropwise to mix the two evenly. The mixed solution is stirred and heated to the reaction temperature until the mixed solution becomes colorless and transparent, i.e., the first mixed solution.
[0076] During the preparation of the first mixed solution, as an optional implementation of the technical solution of the present invention, the heating method can be a water bath or an oil bath, the heating temperature is 30-50°C; the magnetic stirring time is 10-30min, and the magnetic rotor stirring speed is 200-300rpm.
[0077] As an optional implementation of the technical solution of the present invention, the amount of the titanium source in the first mixed solution is 3.4 ml, and the amount of the ethylene glycol solution is 30 ml. The ethylene glycol solution is mainly used to better dissolve the titanium source, so the specific amounts of the titanium source and the ethylene glycol solution in the first mixed solution are not limited thereto, and can be adjusted according to experimental needs, or can be proportionally enlarged according to the experimental scale.
[0078] As an optional implementation of the technical solution of the present invention, in step (a), the nickel source includes nickel acetate tetrahydrate, nickel nitrate or nickel chloride.
[0079] As an optional implementation of the technical solution of the present invention, in step (a), the method for preparing the second mixed solution comprises the following steps:
[0080] Appropriate amounts of ethylene glycol solution and nickel source are weighed respectively, and after the two are fully stirred and mixed, the mixed solution is heated to the reaction temperature.
[0081] Specifically, a proper amount of ethylene glycol (CH2OH)2 solution is measured using a pipette, and a proper amount of nickel acetate tetrahydrate (Ni(CH3COO)2·4H2O) particles are weighed using an electronic balance and added to the ethylene glycol solution, and then a magnetic rotor is used for magnetic stirring until the nickel acetate tetrahydrate particles are completely dissolved in the ethylene glycol solution to obtain a uniform light green mixed solution, i.e., the second mixed solution.
[0082] During the preparation of the second mixed solution, as an optional implementation of the technical solution of the present invention, the heating method can be a water bath or an oil bath, the heating temperature is 30-50°C; the magnetic stirring time is 30-50min, and the magnetic rotor stirring speed is 250-450rpm.
[0083] As an optional implementation of the technical solution of the present invention, the amount of the nickel source in the second mixed solution is 1.43g, and the amount of the ethylene glycol solution is 20ml. The ethylene glycol solution is mainly used to better dissolve the nickel source, so the specific amounts of the nickel source and the ethylene glycol solution in the second mixed solution are not limited thereto, and can be adjusted according to experimental needs, or can be proportionally enlarged according to the experimental scale.
[0084] As an optional embodiment of the technical solution of the present invention, in step (b), the stirring speed is 250-450rpm, the time is 10-12h, and the reaction temperature is 30-50°C. Typical but non-limiting stirring speeds are 250rpm, 280rpm, 300rpm, 320rpm, 350rpm, 380rpm, 400rpm, 420rpm or 450rpm, etc. Typical but non-limiting reaction temperatures are 30°C, 32°C, 35°C, 38°C, 40°C, 42°C, 45°C, 48°C or 50°C, etc.; typical but non-limiting reaction times are 10h, 11h or 12h, etc. By controlling the relevant parameters of stirring, it is possible to ensure that the nickel source and the titanium source are fully reacted in the ethylene glycol solvent.
[0085] As an optional implementation of the technical solution of the present invention, in step (b), the second mixed solution provided in step (a) (for example, a light green mixed solution formed by mixing ethylene glycol (CH2OH)2 solution and Ni(CH3COO)2·4H2O particles) is slowly poured into the first mixed solution provided in step (a) (for example, a colorless transparent solution formed by mixing ethylene glycol (CH2OH)2 solution and tetrabutyl titanate Ti(OC4H9)4 solution), and the mixed solution is magnetically stirred and heated to the reaction temperature at the same time.
[0086] As an optional implementation of the technical solution of the present invention, in step (c), the solution product is filtered (such as suction filtration) to perform solid-liquid separation.
[0087] As an optional implementation of the technical solution of the present invention, in step (c), the solvent used for filtering and / or washing includes anhydrous ethanol. Selecting anhydrous ethanol solvent for suction filtration and washing can effectively remove the solvent and impurities on the surface of the hydrothermal product.
[0088] As an optional embodiment of the technical solution of the present invention, in step (c), the drying is vacuum drying, the vacuum drying temperature is 60-80°C, and the time is 10-12h. Typical but non-limiting vacuum drying temperatures are 60°C, 62°C, 65°C, 68°C, 70°C, 72°C, 75°C, 78°C or 80°C, and typical but non-limiting vacuum drying times are 10h, 11h or 12h, etc.
[0089] As an optional implementation of the technical solution of the present invention, in step (d), the calcination temperature is 500-600°C, the calcination time is 2.5-3h, and the heating rate to the calcination temperature is 3-8°C / min.
[0090] Typical but non-limiting calcination temperatures are 500°C, 520°C, 550°C, 550°C, 560°C, 580°C or 600°C, etc., and typical but non-limiting calcination times are 2.5h, 2.8h or 3h, etc. Typical but non-limiting heating rates are 3°C / min, 4°C / min, 5°C / min, 6°C / min, 7°C / min or 8°C / min, etc.
[0091] As an optional embodiment of the technical solution of the present invention, in step (d), the protective atmosphere includes at least one of nitrogen, argon or helium. This protective atmosphere can prevent the sample from being oxidized during the calcination process. Among them, nitrogen is more suitable and has lower cost, so the protective atmosphere is preferably nitrogen.
[0092] As an optional implementation of the technical solution of the present invention, magnesium hydride is prepared by hydrogenation combustion synthesis. For example, the preparation method of magnesium hydride comprises the following steps:
[0093] The raw magnesium powder is placed in a reaction boat in a furnace chamber for reaction; in order to avoid the presence of impurity gases such as oxygen during the reaction, the furnace chamber pressure is first pumped down to 25Pa by a vacuum pump and then filled with 0.2MPa argon for three times to ensure the purity of the gas in the furnace chamber, followed by filling with 2.0MPa hydrogen; then, the furnace chamber is heated from room temperature to 580°C and kept warm for 2h, with a heating rate of 10°C / min; then, the heating system is turned off and naturally cooled to 340°C and kept warm for 8h. During the reaction, the pressure can be adjusted to always keep the hydrogen pressure at 2.0MPa; finally, the heating and hydrogen input are stopped, and the chamber is naturally cooled to room temperature; preferably, the raw magnesium powder does not need to be pre-milled or pressed.
[0094] As an optional implementation of the technical solution of the present invention, the initial desorption temperature of the magnesium-based hydrogen storage material is as low as 185°C.
[0095] According to a second aspect of the present invention, there is also provided a method for preparing the bimetallic catalyzed magnesium-based hydrogen storage material according to the first aspect of the present invention, comprising the following steps:
[0096] The bimetallic catalyst TiO2 / C / Ni and magnesium hydride are evenly mixed by ball milling to obtain a magnesium-based hydrogen storage material.
[0097] As a preferred embodiment of the present invention, the bimetallic catalyzed magnesium-based hydrogen storage material of the present invention is prepared by the following method:
[0098] S1: Preparation of Ti-EG-Ni precursor catalyst
[0099] S11: respectively measure an appropriate amount of ethylene glycol (CH2OH)2 solution and an appropriate amount of tetrabutyl titanate Ti(OC4H9)4 solution, mix the two evenly, stir and heat to the reaction temperature at the same time;
[0100] Specifically, a proper amount of ethylene glycol (CH2OH)2 solution and a proper amount of tetrabutyl titanate Ti(OC4H9)4 solution are measured using a pipette, and the tetrabutyl titanate solution is added dropwise while the ethylene glycol solution is magnetically stirred by a magnetic rotor to mix the two uniformly, and the mixed solution is heated to a reaction temperature while stirring until the mixed solution is colorless and transparent, i.e., the first mixed solution;
[0101] In the above preparation method, as a preferred embodiment, in step S11, the content of the ethylene glycol solvent is 30 mL.
[0102] In the above preparation method, as a preferred embodiment, in step S11, the heating method can be a water bath or an oil bath, and the heating temperature is controlled at 30-50°C; the magnetic stirring time is 10-30min, and the magnetic rotor stirring speed is 200-300rpm.
[0103] S12: respectively measuring an appropriate amount of ethylene glycol solution and an appropriate amount of nickel source, stirring and mixing the two, and then heating the mixed solution to a reaction temperature;
[0104] Specifically, a proper amount of ethylene glycol (CH2OH)2 solution is measured using a pipette, and a proper amount of nickel acetate tetrahydrate (Ni(CH3COO)2·4H2O) particles are weighed using an electronic balance and added to the ethylene glycol solution, and then a magnetic rotor is used for magnetic stirring until the nickel acetate tetrahydrate particles are completely dissolved in the ethylene glycol solution to obtain a uniform light green mixed solution, i.e., the second mixed solution;
[0105] In the above preparation method, as a preferred embodiment, in step S12, the ethylene glycol solvent content is 20 mL, the magnetic stirring time is 30-50 min, and the magnetic rotor stirring speed is 250-450 rpm;
[0106] S13: Slowly pour the uniform solution obtained in S12 into the uniform solution in S11, stir continuously and keep warm at 30°C for 12h.
[0107] The second mixed solution obtained in S12 (i.e., a light green mixed solution formed by mixing ethylene glycol (CH2OH)2 solution and Ni(CH3COO)2·4H2O particles) is slowly poured into the first mixed solution in S11 (i.e., a colorless transparent solution formed by mixing ethylene glycol (CH2OH)2 solution and tetrabutyl titanate Ti(OC4H9)4 solution), and the mixed solution is heated to the reaction temperature by magnetic stirring at the same time;
[0108] In the above preparation method, as a preferred embodiment, in step S13, the magnetic stirring speed is 250-450 rpm, the time is 10-12 h, and the reaction temperature is 30-50 ° C. Long-term stirring can ensure that the nickel source and the titanium source are fully reacted in the ethylene glycol solvent;
[0109] S14: The solution product obtained in S13 is filtered and washed, and the product is dried in a vacuum oven to obtain a light green catalyst precursor Ti-EG-Ni powder, whose microscopic morphology is a smooth tubular micelle structure (visible attached Figure 2a );
[0110] In the above preparation method, as a preferred embodiment, anhydrous ethanol is used as a solvent for suction filtration and washing in step S14, which can effectively remove the solvent and impurities on the surface of the hydrothermal product; the product is dried in a vacuum oven, and the drying temperature is controlled at 60-80°C for 10-12h;
[0111] The synthesis mechanism of the catalyst precursor in the present invention is as follows: the nickel source and the titanium source are dissolved in 50 mL of ethylene glycol at a molar ratio of 1:1 (the nickel source is Ni(CH3COO)2·4H2O and the titanium source is Ti(OC4H9)4), and a clear light green solution is formed at room temperature. Ethylene glycol acts as a solvent and a ligand to react with Ti 4+ and Ni 2+ The reaction formed a smooth tubular micelle structure Ti-EG-Ni, and the precursor sample synthesis XRD showed that the attached Figure 1b .
[0112] S2: Preparation of TiO2 / C / Ni catalyst
[0113] S21: The dried product Ti-EG-Ni precursor in S1 is calcined in a closed tube furnace; specifically, under a nitrogen atmosphere, the dried Ti-EG-Ni precursor is placed in a closed tube furnace with a circulating nitrogen atmosphere and calcined at high temperature to finally obtain a black powder TiO2 / C / Ni, the microscopic morphology of which is a rough nanorod-like structure, as shown in the attached Figure 2b (Here, nitrogen is used as the calcination atmosphere, which has the advantages of low price, cost reduction, and obvious calcination effect);
[0114] In the above preparation method, as a preferred embodiment, in step S21, the precursor calcination heating rate is 5°C / min, the calcination temperature is 500-600°C, and the calcination time is 2.5-3h, and finally a black TiO2 / C / Ni powder is obtained;
[0115] Catalyst synthesis mechanism: Based on the successful synthesis of the precursor, it is calcined in a nitrogen atmosphere. As the ethylene glycol in the organic matter is thermally decomposed into carbon materials, the morphology changes from smooth tubular micelles to rough rod-like structures, and its lateral and longitudinal dimensions are halved. Nickel and titanium dioxide nanoparticles are evenly distributed in the carbon matrix, and many small nanoparticles are dispersed on the rough surface. The catalyst sample synthesis XRD and SEM can show the presence of attached Figure 1b , Figure 1c and Figure 2a , Figure 2b .
[0116] S3: Preparation of MgH2: MgH2 is prepared by hydrogenation combustion synthesis (HCS);
[0117] In the above-mentioned method for preparing the solid hydrogen storage composite material, as a preferred embodiment, in the step S3, the preparation of MgH2 comprises the following steps:
[0118] The raw magnesium powder is placed in a reaction boat in a furnace chamber for reaction; in order to avoid the presence of impurity gases such as oxygen during the reaction, the furnace chamber pressure is first pumped down to 25Pa by a vacuum pump and then filled with 0.2MPa argon for three times to ensure the purity of the gas in the furnace chamber, followed by filling with 2.0MPa hydrogen; then, the furnace chamber is heated from room temperature to 580°C and kept warm for 2h, with a heating rate of 10°C / min; then, the heating system is turned off and naturally cooled to 340°C and kept warm for 8h. During the reaction, the pressure can be adjusted to always keep the hydrogen pressure at 2.0MPa; finally, the heating and hydrogen input are stopped, and the chamber is naturally cooled to room temperature; preferably, the raw magnesium powder does not need to be pre-milled or pressed.
[0119] S4: Preparation of MgH2-TiO2 / C / Ni composite material: TiO2 / C / Ni catalysts with different mass fractions were introduced into the prepared MgH2 by ball milling to obtain MgH2-TiO2 / C / Ni composite material.
[0120] In the preparation method of the above-mentioned solid hydrogen storage composite material, as a preferred embodiment, in the step S4, (x=0, 3, 5, 8, 10)x wt% TiO2 / C / Ni is added to the obtained MgH2 according to different mass ratios, and the mixture is evenly mixed by ball milling to prepare the MgH2-TiO2 / C / Ni composite material.
[0121] Preparation ideas of MgH2-TiO2 / C / Ni composite materials: Considering the cost-effectiveness and excellent catalytic performance of nickel-based and titanium-based catalysts, as well as the protective properties of carbon materials on nanomaterials, the present invention synthesizes Ti-EG-Ni bimetallic organic crystals through a unique self-assembly process. Based on the precursor, a rod-shaped TiO2 / C / Ni nanostructure is generated by calcination treatment under a nitrogen atmosphere, in which TiO2 and Ni nanoparticles are uniformly embedded in the carbon matrix. By high-energy ball milling and introducing the catalyst into the MgH2 system, the prepared MgH2-TiO2 / C / Ni composite material exhibits excellent hydrogen storage performance and hydrogen absorption and desorption cycle stability. Based on the microstructure of the material (attached Figure 3a , Figure 3b , Figure 4 , Figure 5 and Figure 6 ) and hydrogen storage performance (attached Figure 7 , Figure 8 , Figure 9a , Figure 9b , Fig.10a , Fig.10b , Fig.11a and Fig.11b ), and a possible catalytic mechanism was proposed.
[0122] As an optional implementation of the technical solution of the present invention, the mass ratio of the bimetallic catalyst TiO2 / C / Ni and magnesium hydride is (10wt% / 90wt%) to (0wt% / 100wt%), that is, (10-0): (90-100). Wherein, the mass fraction of the bimetallic catalyst TiO2 / C / Ni is not equal to 0wt%.
[0123] As an optional implementation manner of the technical solution of the present invention, the ball-to-material ratio used in the ball milling process is (25-35):1 (for example, 25:1, 28:1, 30:1, 32:1 or 35:1, etc.), the rotation speed is 350-450rpm (for example, 350rpm, 400rpm or 450rpm, etc.), the ball milling is 8-12h (for example, 8h, 10h or 12h, etc.), alternating forward and reverse rotation, and stopping for 6min every 30min of work.
[0124] According to the third aspect of the present invention, there is also provided the use of the bimetallic catalyzed magnesium-based hydrogen storage material of the first aspect of the present invention or the bimetallic catalyzed magnesium-based hydrogen storage material prepared by the preparation method of the second aspect of the present invention in the field of hydrogen storage.
[0125] In view of the advantages of the bimetallic catalyzed magnesium-based hydrogen storage material of the present invention, it has good application prospects in the field of hydrogen storage.
[0126] The present invention will be further described in detail below with reference to specific embodiments and comparative examples.
[0127] Example 1
[0128] This embodiment provides a bimetallic catalyzed magnesium-based hydrogen storage material, wherein the magnesium-based hydrogen storage material is a composite formed by MgH2 and a catalyst;
[0129] Among them, the catalyst is a bimetallic catalyst TiO2 / C / Ni formed by loading nickel and titanium dioxide on a carbon matrix. The mass content of the bimetallic catalyst TiO2 / C / Ni in the magnesium-based hydrogen storage material is 8wt%, so the magnesium-based hydrogen storage material can be abbreviated as MgH2-8 wt.%TiO2 / C / Ni.
[0130] Taking the mass of the bimetallic catalyst TiO2 / C / Ni as 100%, the bimetallic catalyst TiO2 / C / Ni is designed to contain the following mass fractions of the components: the mass fraction of nickel is 30-35%, the mass fraction of titanium dioxide is 40-45%, and the mass fraction of carbon is 20-30%.
[0131] The preparation method of the bimetallic catalyzed magnesium-based hydrogen storage material of this embodiment comprises the following steps:
[0132] S1: Preparation of Ti-EG-Ni precursor
[0133] S11: Use a pipette to measure 3.4 mL of Ti(OC4H9)4 solution, add it dropwise into 30 mL of ethylene glycol solution, stir magnetically (magnetic rotor stirring speed 200-300 rpm), and heat the solution in a water bath to 30°C for 30 min to achieve complete mixing, thereby obtaining a first mixed solution;
[0134] S12: 1.43 g Ni(CH3COO)2·4H2O was weighed on an electronic balance and slowly added to 20 ml ethylene glycol solution. The solution was heated to 30° C. in a water bath for 30 min while being magnetically stirred (magnetic rotor stirring speed 250-450 rpm) to completely dissolve the particles and mix the solution evenly, thereby obtaining a second mixed solution.
[0135] S13: slowly pour the second mixed solution obtained in S12 into the first mixed solution in S11, continuously stir (stirring speed 250-450 rpm) and heat in a water bath to 30° C. for 12 h to obtain a mixed solution product;
[0136] S14: The mixed solution product in S13 was filtered and washed with anhydrous ethanol, and the product was dried in a vacuum oven at 60° C. for 12 h to obtain a light green catalyst precursor Ti-EG-Ni;
[0137] S2: Preparation of catalyst TiO2 / C / Ni
[0138] S21: In a nitrogen atmosphere, the dried precursor TiO2 / C / Ni was heated to 500°C at 5°C / min and calcined at high temperature for 3 hours to finally obtain a black catalyst TiO2 / C / Ni powder;
[0139] S3: Preparation of MgH2
[0140] MgH2 was synthesized by hydrogenation combustion synthesis (HCS). First, Mg powder was heated from room temperature to 580°C and kept warm for 2 hours at a heating rate of 10°C / min. Then, the heating system was turned off and naturally cooled to 340°C and kept warm for 8 hours. During the reaction, the pressure could be adjusted to always maintain a hydrogen pressure of 2.0 MPa. Finally, the heating and hydrogen input were stopped, and the mixture was naturally cooled to room temperature to obtain MgH2.
[0141] S4: Preparation of MgH2-8 wt.%TiO2 / C / Ni
[0142] TiO2 / C / Ni was added to MgH2 according to the mass percentage formula, and the mixture was mixed by ball milling to obtain a magnesium-based hydrogen storage material MgH2-8 wt.% TiO2 / C / Ni (MgH2-8 wt.% TiO2 / C / Ni composite material); wherein the ball-to-material ratio was 30:1, the rotation speed was 400 rpm, the ball milling was performed for 10 hours, alternating forward and reverse rotations, and the rotation was stopped for 6 minutes after every 30 minutes of operation.
[0143] Example 2
[0144] This embodiment provides a bimetallic catalyzed magnesium-based hydrogen storage material. Except that the mass content of the bimetallic catalyst TiO2 / C / Ni in the magnesium-based hydrogen storage material is adjusted from 8wt.% to 3wt.%, the remaining raw material composition is the same as that in Example 1.
[0145] The preparation method of the bimetallic catalyzed magnesium-based hydrogen storage material of this embodiment is the same as that of Example 1, except that the mass ratio of TiO2 / C / Ni added to MgH2 in step S4 is adjusted accordingly.
[0146] Example 3
[0147] This embodiment provides a bimetallic catalyzed magnesium-based hydrogen storage material. Except that the mass content of the bimetallic catalyst TiO2 / C / Ni in the magnesium-based hydrogen storage material is adjusted from 8wt.% to 5wt.%, the remaining raw material composition is the same as that in Example 1.
[0148] The preparation method of the bimetallic catalyzed magnesium-based hydrogen storage material of this embodiment is the same as that of Example 1, except that the mass ratio of TiO2 / C / Ni added to MgH2 in step S4 is adjusted accordingly.
[0149] Example 4
[0150] This embodiment provides a bimetallic catalyzed magnesium-based hydrogen storage material. Except that the mass content of the bimetallic catalyst TiO2 / C / Ni in the magnesium-based hydrogen storage material is adjusted from 8wt.% to 10wt.%, the remaining raw material composition is the same as that in Example 1.
[0151] The preparation method of the bimetallic catalyzed magnesium-based hydrogen storage material of this embodiment is the same as that of Example 1, except that the mass ratio of TiO2 / C / Ni added to MgH2 in step S4 is adjusted accordingly.
[0152] Comparative Example 1
[0153] This comparative example provides a magnesium-based hydrogen storage material, specifically MgH2 (ie, no bimetallic catalyst TiO2 / C / Ni is added), and the preparation method of MgH2 is the same as step S3 in the preparation method of Example 1.
[0154] Comparative Example 2
[0155] This comparative example provides a metal-catalyzed magnesium-based hydrogen storage material, which is a composite formed by MgH2 and catalyst Ni. The mass content of Ni in the magnesium-based hydrogen storage material is 8 wt.%, so the magnesium-based hydrogen storage material can be abbreviated as MgH2-8 wt.%Ni.
[0156] The preparation method of the metal-catalyzed magnesium-based hydrogen storage material of this comparative example comprises the following steps:
[0157] S1: Your Preparation
[0158] The Ni used here is nano-nickel, which can be prepared or purchased.
[0159] S2: Preparation of MgH2
[0160] The preparation method of MgH2 is the same as that in step S3 of Example 1.
[0161] S3: Preparation of MgH2-8 wt.%Ni
[0162] Nano nickel was added to MgH2 according to a mass percentage formula, and mixed by ball milling to obtain a magnesium-based hydrogen storage material MgH2-8 wt.%Ni; wherein the ball-to-material ratio was 30:1, the rotation speed was 400 rpm, the ball milling was performed for 10 hours, alternating forward and reverse rotations, and the work was stopped for 6 minutes every 30 minutes.
[0163] Comparative Example 3
[0164] This comparative example provides a metal-catalyzed magnesium-based hydrogen storage material, which is a composite formed by MgH2 and catalyst TiO2 / C. The mass content of TiO2 / C in the magnesium-based hydrogen storage material is 8wt%, so the magnesium-based hydrogen storage material can be abbreviated as MgH2-8 wt.%TiO2 / C.
[0165] The preparation method of the metal-catalyzed magnesium-based hydrogen storage material of this comparative example comprises the following steps:
[0166] S1: Preparation of Ti-EG precursor
[0167] S11: Use a pipette to measure 3.4 mL of Ti(OC4H9)4 solution, add it dropwise into 30 mL of ethylene glycol solution, stir magnetically (magnetic rotor stirring speed 200-300 rpm), and heat the solution in a water bath to 30°C for 30 min to achieve complete mixing, thereby obtaining a first mixed solution;
[0168] S12: The first mixed solution obtained in S11 is continuously stirred (stirring speed 250-450 rpm) and heated to 30° C. in a water bath for 12 h to obtain a mixed solution product;
[0169] S13: The mixed solution product in S12 is filtered and washed with anhydrous ethanol, and the product is dried in a vacuum oven at 60° C. for 12 h to obtain a precursor Ti-EG;
[0170] S2: Preparation of catalyst TiO2 / C
[0171] S21: In a nitrogen atmosphere, the dried precursor TiO2 / C was heated to 500°C at 5°C / min and calcined at high temperature for 3 hours to finally obtain a black catalyst TiO2 / C powder;
[0172] S3: Preparation of MgH2
[0173] The preparation method of MgH2 is the same as that in step S3 of Example 1.
[0174] S4: Preparation of MgH2-8 wt.% TiO2 / C
[0175] TiO2 / C was added to MgH2 according to the mass percentage formula, and mixed by ball milling to obtain the magnesium-based hydrogen storage material MgH2-8 wt.% TiO2 / C; wherein, the ball-to-material ratio was 30:1, the rotation speed was 400 rpm, the ball milling was performed for 10 hours, alternating forward and reverse rotations, and stopping for 6 minutes every 30 minutes of work.
[0176] The performance of the precursor Ti-EG-Ni, the catalyst TiO2 / C / Ni, and the magnesium-based hydrogen storage material provided in the embodiments or comparative examples of the present invention was tested in various aspects, as follows:
[0177] (1) Taking Example 1 as an example, the synthesis process of the catalyst TiO2 / C / Ni is briefly described. Figure 1a shown. Figure 1a It shows the process of nickel acetate and tetrabutyl titanate being dissolved in ethylene glycol (ethylene glycol is a solvent and chelating agent between ions), forming the precursor Ti-EG-Ni through continuous stirring, and then calcining to form the final catalyst product TiO2 / C / Ni.
[0178] At the same time, XRD tests were performed on the precursor Ti-EG-Ni and the catalyst TiO2 / C / Ni. The XRD spectrum of the precursor Ti-EG-Ni (also expressed as Ni-Ti-EG) is shown in Figure 1b As shown, it shows that the catalyst precursor was successfully synthesized. The XRD spectrum of the catalyst TiO2 / C / Ni is shown in Figure 1c As shown, the diffraction peaks of the Ni (JCPDS.#87-0712) FCC phase can be seen, located at 44.6°, 51.9° and 76.5°: the broad peak of about 20° is attributed to the amorphous carbon formed in situ (produced by the pyrolysis of ethylene glycol). The peaks at 25.3° (101) and 48.1° (200) correspond to anatase TiO2 (JCPDS#78-2486), while the diffraction peaks corresponding to the (110), (101), (111), (211), (220) and (301) planes of TiO2 (JCPDS#99-0090) appear at 27.5°, 36.1°, 41.2°, 54.4°, 56.8° and 69.2°, respectively, indicating the successful preparation of the catalyst TiO2 / C / Ni in Example 1.
[0179] The microstructures of the precursor Ti-EG-Ni and the catalyst TiO2 / C / Ni prepared in Example 1 were also tested. Figure 2a and Figure 2b They are the SEM images of the precursor Ti-EG-Ni and the catalyst TiO2 / C / Ni. Figure 2a It can be seen that ethylene glycol, Ni 2+ and Ti 4+ Combined to form a precursor Ti-EG-Ni with a length of 2-4 μm, a diameter of 500-800 nm and a smooth nanotube micelle structure. Figure 2b As shown in the figure, after the precursor Ti-EG-Ni is calcined at high temperature, the prepared catalyst TiO2 / C / Ni is a nanorod-like structure with a rough surface, with a length of about 0.5-1μm and a diameter of about 200-300nm. In addition, due to the uniform distribution of nickel and TiO2 nanoparticles in the carbon matrix, many small nanoparticles are dispersed on the rough surface, highlighting the key role of ethylene glycol as an organic solvent in the formation of ultrafine nanoparticles.
[0180] (2) In order to explore the potential catalytic mechanism of the catalyst TiO2 / C / Ni, XRD analysis was performed on the magnesium-based hydrogen storage material MgH2-8 wt.% TiO2 / C / Ni prepared in Example 1. Figure 3a and Figure 3b The XRD patterns of magnesium-based hydrogen storage material MgH2-8 wt.%TiO2 / C / Ni in different states (ball-milled, dehydrogenated, and rehydrogenated) are shown. In the ball-milled state, the main phases of the magnesium-based hydrogen storage material are MgH2, Ni, and TiO2. After dehydrogenation, the diffraction peak of MgH2 disappears, and Mg becomes the dominant phase, indicating that the magnesium-based hydrogen storage material MgH2-8 wt.%TiO2 / C / Ni has been completely dehydrogenated. It is worth noting that Ni is transformed into the diffraction peak of Mg2Ni, indicating that Mg and Ni react to form Mg2Ni during the dehydrogenation process. The diffraction peak of TiO2 is still visible, and the appearance of MgTi2O4 indicates that the reaction between MgH2 and TiO2 forms a Ti-containing oxide rock salt phase during the dehydrogenation process. In the rehydrogenated samples, the dominant phase Mg was transformed into MgH2, while a small amount of unhydrogenated Mg, TiO2, MgTi2O4 and Mg2NiH4 (Mg2Ni after hydrogen absorption) were observed.
[0181] The microstructure and elemental composition of the rehydrogenated magnesium-based hydrogen storage material MgH2-8 wt.% TiO2 / C / Ni were examined. Figure 4 , Figure 5 and Figure 6 As shown. Among them, Figure 4 This is the HRTEM image of the magnesium-based hydrogen storage material MgH2-8 wt.% TiO2 / C / Ni prepared in Example 1 in the re-hydrogenated state. Figure 5 is the corresponding SAED image, Figure 6 is the corresponding EDS element distribution diagram. Figure 5 and Figure 6 The lattice fringes and diffraction rings prove that the phase of magnesium-based hydrogen storage materials changes after rehydriding. In addition to the main phase MgH2, new phases Mg2Ni, TiO2, MgTi2O4 and TiH2 are generated. Figure 6 It can be seen that the catalyst is evenly distributed on the surface of the Mg substrate, providing favorable conditions for efficient catalysis.
[0182] The above XRD and TEM characterizations show that during the hydrogen absorption and release process, the magnesium-based hydrogen storage material MgH2-TiO2 / C / Ni of the present invention forms a multi-element, multi-valent environment (including Mg2Ni / Mg2NiH4 (hydrogen pump effect) and multivalent Ti), the elements are evenly distributed, and the protection mechanism provided by the carbon material, these factors together promote the excellent hydrogen storage performance of MgH2.
[0183] (3) In order to determine the optimal catalyst TiO2 / C / Ni ratio in the magnesium-based hydrogen storage material MgH2-x wt.% TiO2 / C / Ni, DSC tests were performed on the catalyst TiO2 / C / Ni doped MgH2 with different ratios (x=0, 3, 5, 8, 10) prepared in Examples 1-4 and Comparative Example 1. Figure 7 As shown in the figure. The results show that the dehydrogenation peak temperature of pure MgH2 is 392.3℃. As the content of catalyst TiO2 / C / Ni increases from 3% to 5%, the peak temperature of hydrogen desorption decreases from 307.3℃ to 294.8℃, which shows the positive role of the catalyst in improving the dehydrogenation performance of MgH2. When the content of catalyst TiO2 / C / Ni is 8wt.%, the magnesium-based hydrogen storage material exhibits excellent comprehensive dehydrogenation performance, rapidly releasing hydrogen at 266.8℃. Since the hydrogen desorption performance did not improve significantly when TiO2 / C / Ni increased to 10wt.%, the MgH2-8% TiO2 / C / Ni composite material was selected for further study.
[0184] (4) In order to illustrate the hydrogen desorption effect achieved by the magnesium-based hydrogen storage material MgH2-TiO2 / C / Ni of the present invention, the TPD curves (programmed desorption curves) of the magnesium-based hydrogen storage materials (MgH2-8wt.%TiO2 / C / Ni, MgH2-8wt.%Ni and MgH2-8wt.%TiO2 / C) prepared in Example 1, Comparative Example 2 and Comparative Example 3 were detected. Figure 8 As shown. It can be seen from the figure that Ni-doped MgH2 begins to desorb hydrogen at 210°C and completely desorbs 6.7% H2 at 325°C. MgH2 doped with TiO2 / C begins to desorb hydrogen at 220°C and completely desorbs 6.7wt.% H2 at 350°C. It is worth noting that the magnesium-based hydrogen storage material MgH2-8% TiO2 / C / Ni exhibits the lowest initial desorption temperature of 185°C, desorbs 6.5wt.% H2 at 300°C, and reaches 97% of the final hydrogen desorption amount (6.72wt.% H2). Compared with using Ni and TiO2 as catalysts alone, TiO2 / C / Ni exhibits superior catalytic performance for MgH2 desorption, indicating that Ni and TiO2 have a synergistic catalytic effect on MgH2 dehydrogenation.
[0185] (5) Figure 9a, Figure 9b Used to calculate the dehydrogenation activation energy of the magnesium-based hydrogen storage material MgH2-8wt.%TiO2 / C / Ni provided in Example 1 of the present invention.
[0186] The Kissinger equation is a commonly used method for analyzing thermal analysis data to determine activation energy. It estimates the activation energy (E) by examining the relationship between the peak temperature (T) and the heating rate (β). a ). The expression of the equation is as follows:
[0187]
[0188] Where β represents the heating rate, T represents the peak temperature, R is the gas constant, C is the linear constant, and E a represents the apparent activation energy.
[0189] according to Figure 9a , Figure 9b According to the DSC data in, the apparent activation energy of the magnesium-based hydrogen storage material MgH2-8wt.%TiO2 / C / Ni was calculated to be 60.526 kJ / mol, which is 61% lower than that of pure MgH2 (156.4 kJ / mol), indicating that the addition of catalyst TiO2 / C / Ni significantly reduces the apparent activation energy of MgH2 dehydrogenation.
[0190] At the same time, as shown in Table 1 below, the dehydrogenation activation energy of the bimetallic catalyst TiO2 / C / Ni of the present invention and other types of catalysts disclosed in the prior art after modification of MgH2 are compared.
[0191] Table 1
[0192] sample Dehydrogenation activation energy (kJ / mol) <![CDATA[MgH2-8wt.%TiO2 / C / Ni]]> 60.537 <![CDATA[MgH2-8wt.%MnTiO3]]> 72.06 <![CDATA[MgH2-10wt.%Ni@C@CeO2]]> 82.63 <![CDATA[MgH2-10wt.%70TiO2@rGO]]> 86.7 <![CDATA[MgH2-10wt.%NiMoO4]]> 85.88 <![CDATA[MgH2-5wt.%Ni6MnO8@rGO]]> 115.15 <![CDATA[MgH2-5wt.%Ti-CoO@C]]> 137.76 <![CDATA[MgH2-10wt.%FeNi@3DG]]> 88.4
[0193] Note: “70” in MgH2-10 wt.%70TiO2@rGO represents the theoretical mass fraction of TiO2;
[0194] , “DG” in MgH2-10 wt.%FeNi@3DG stands for three-dimensional graphene.
[0195] As can be seen from Table 1, the bimetallic catalyst TiO2 / C / Ni of the present invention accelerates the hydrogen absorption and desorption kinetics of MgH2, exhibits better hydrogen storage performance than other catalysts, and has a better effect on improving the performance of MgH2.
[0196] (6) Fig.10a , Fig.10bThe isothermal dehydrogenation and hydrogenation curves of the magnesium-based hydrogen storage material MgH2-8 wt.% TiO2 / C / Ni at different temperatures are shown. The initial hydrogen pressure for absorption is 3MPa, and the initial hydrogen pressure for desorption is 0.005MPa. It can be seen from the figure that the magnesium-based hydrogen storage material MgH2-8 wt.% TiO2 / C / Ni in the state of complete hydrogen absorption released 6.17wt.% H2 within 300 seconds at 300°C, reaching 94.6% (6.52wt.% H2) of the complete dehydrogenation capacity; the magnesium-based hydrogen storage material MgH2-8 wt.% TiO2 / C / Ni quickly absorbed 5.72wt.% H2 within 20 seconds at 150°C, and reached 6.18wt.% H2 within 1000 seconds after complete dehydrogenation, showing higher dehydrogenation and hydrogen absorption kinetic characteristics.
[0197] At the same time, the cyclic stability of hydrogen absorption and desorption of the magnesium-based hydrogen storage material MgH2-8 wt.%TiO2 / C / Ni was tested, as shown in Figure 11. Fig.11a and Fig.11b The figure is the change of hydrogen absorption and desorption capacity of the magnesium-based hydrogen storage material MgH2-8wt.%TiO2 / C / Ni after 50 cycles of hydrogen absorption and desorption at 275°C. It can be found that after 50 cycles of hydrogen absorption and desorption, the reversible capacity of the MgH2-8 wt.%TiO2 / C / Ni composite material only drops from 6.35wt.%H2 to 5.97wt.%H2, showing a capacity retention rate of 94% and a capacity loss of 0.12wt.% per cycle. Therefore, it can be clearly seen that the magnesium-based hydrogen storage material MgH2-8 wt.%TiO2 / C / Ni of the present invention has excellent cycle stability.
[0198] From the above detection and analysis, it can be seen that the magnesium-based hydrogen storage material provided by the present invention, especially MgH2-8wt.%TiO2 / C / Ni, exhibits excellent catalytic performance, with an initial dehydrogenation temperature of 185°C, and maintains good kinetic stability and capacity retention after multiple cycles, with a capacity decay rate of only 6% after 50 cycles. It also has excellent hydrogen storage performance: it can absorb 5.72wt.%H2 within 20 seconds at 150°C, and even at a low temperature of 75°C, it can absorb 4.33wt.%H2 within 3000 seconds. At the same time, it can release 6.17wt.%H2 within 300 seconds at 300°C, and 2.1wt.%H2 within 3000 seconds at 225°C.
[0199] In general, the application of the catalyst TiO2 / C / Ni to the modification of the hydrogen storage performance of MgH2 achieved a high-efficiency catalytic effect, effectively solved the problem of slow low-temperature hydrogen absorption and high-temperature dehydrogenation kinetics, and at the same time improved the hydrogen absorption and desorption cycle stability of the composite material.
[0200] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention are within the scope of protection of the pending claims of the present invention.
Claims
1. A bimetallic catalyzed magnesium-based hydrogen storage material, characterized in that: The magnesium-based hydrogen storage material is a composite formed by magnesium hydride and a catalyst; The catalyst is a bimetallic catalyst TiO2 / C / Ni formed by loading nickel and titanium dioxide on a carbon matrix.
2. The bimetallic catalyzed magnesium-based hydrogen storage material according to claim 1, characterized in that: The mass content of the catalyst in the magnesium-based hydrogen storage material is 0-10wt% and not 0wt%, preferably 3-8wt%, and more preferably 8wt%.
3. The bimetallic catalyzed magnesium-based hydrogen storage material according to claim 1, characterized in that: Taking the mass of the bimetallic catalyst TiO2 / C / Ni as 100%, the bimetallic catalyst TiO2 / C / Ni comprises the following components in mass fractions: Ni 30-35%, TiO2 40-45%, and C20-30%.
4. The bimetallic catalyzed magnesium-based hydrogen storage material according to claim 1, characterized in that: The preparation method of the bimetallic catalyst TiO2 / C / Ni comprises the following steps: (a) providing a first mixed solution formed of a titanium source and an ethylene glycol solution, and a second mixed solution formed of a nickel source and an ethylene glycol solution; (b) slowly adding the second mixed solution into the first mixed solution, stirring and heating to allow the mixture to react, thereby obtaining a mixed solution product; (c) subjecting the mixed solution product to solid-liquid separation, and washing and drying the separated solid product to obtain a precursor Ti-EG-Ni; (d) The precursor Ti-EG-Ni is calcined in a protective atmosphere to obtain a bimetallic catalyst TiO2 / C / Ni.
5. The bimetallic catalyzed magnesium-based hydrogen storage material according to claim 4, characterized in that: In step (a), the titanium source includes at least one of tetrabutyl titanate, titanium sulfate or titanium isopropoxide; And / or, in step (a), the nickel source comprises at least one of nickel acetate tetrahydrate, nickel nitrate or nickel chloride; And / or, in step (b), the stirring speed is 250-450 rpm, the time is 10-12 h, and the reaction temperature is 30-50°C.
6. The bimetallic catalyzed magnesium-based hydrogen storage material according to claim 4, characterized in that: In step (c), the solvent used for washing includes anhydrous ethanol; And / or, in step (c), the drying is vacuum drying, the vacuum drying temperature is 60-80° C., and the time is 10-12 h. and / or, in step (d), the calcination temperature is 500-600° C., the calcination time is 2.5-3 h, and the heating rate to the calcination temperature is 3-8° C. / min; And / or, in step (d), the protective atmosphere comprises at least one of nitrogen, argon or helium, preferably nitrogen.
7. The bimetallic catalyzed magnesium-based hydrogen storage material according to any one of claims 1 to 6, characterized in that: The magnesium hydride is prepared by hydrogenation combustion synthesis method; And / or, the initial desorption temperature of the magnesium-based hydrogen storage material is at least 185°C.
8. The method for preparing a bimetallic catalyzed magnesium-based hydrogen storage material according to any one of claims 1 to 7, characterized in that: The following steps are involved: The bimetallic catalyst TiO2 / C / Ni and magnesium hydride are evenly mixed by ball milling to obtain a magnesium-based hydrogen storage material.
9. The method for preparing a bimetallic catalyzed magnesium-based hydrogen storage material according to claim 8, characterized in that: The ball-to-material ratio used in the ball milling process is (25-35):1, the rotation speed is 350-450rpm, the ball milling is 8-12h, alternating forward and reverse rotation, and rest for 6min every 30min of work.
10. Use of the bimetallic catalyzed magnesium-based hydrogen storage material according to any one of claims 1 to 7 or the bimetallic catalyzed magnesium-based hydrogen storage material prepared by the preparation method according to claim 8 or 9 in the field of hydrogen storage.
Citation Information
Cited By
Modified magnesium hydride composite material as well as preparation method and application thereof
CN120681720A
Modified magnesium hydride composite hydrogen storage material and preparation method thereof
CN120757069A
Method for preparing titanium-based double metal oxide semiconductor catalyst and magnesium-based hydrogen storage material
CN122745885A